Reading in a second language cognitive and psycholinguistic issues - Chen, Xi 1974-; Dronjic, Vedran; Helms-Park, Rena (London Routledge, 2016)
Reading in a Second Language offers a comprehensive survey of the phenomenon and process of reading in a second language, with graduate and upper-level undergraduate students in second language acquisition, psycholinguistics, and applied psychology as its primary audience. The book explores reading processes from a number of complementary standpoints, integrating perspectives from fields such as first and second language reading, second language acquisition, linguistics, psycholinguistics, and cognitive neuroscience. The first half examines major factors in second language reading: types of scripts, the cognitive and neural substrates of reading; metalinguistic awareness, word recognition, language transfer, and lexical knowledge. The second part of the book discusses the social and educational contexts in which reading development occurs, including issues related to pedagogy, the use of technology in the classroom, reading disorders, and policy making. Reading in a Second Language provides students with a full, logically organized overview of the primary factors that shape reading development and processes in a second language.
1. Languages and scripts -- 2. Reading and cognition -- 3. Word recognition and spelling -- 4. Cross-language transfer of cognitive and metalinguistic skills. -- 5. Vocabulary and reading -- 6. Higher-level processes in reading -- 7. Reading strategies and knowledge of text structure -- 8. The social context of second language reading -- 9. Reading in a technological age -- 10. Problems with reading.
Includes bibliographical references and index.
Keywords: Reading (Higher education); Second language acquisition; English language -- Study and teaching (Higher) -- Foreign speakers; Reading comprehension; Psycholinguistics